16-(6y-7)+3y=5(y+1)

Simple and best practice solution for 16-(6y-7)+3y=5(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-(6y-7)+3y=5(y+1) equation:


Simplifying
16 + -1(6y + -7) + 3y = 5(y + 1)

Reorder the terms:
16 + -1(-7 + 6y) + 3y = 5(y + 1)
16 + (-7 * -1 + 6y * -1) + 3y = 5(y + 1)
16 + (7 + -6y) + 3y = 5(y + 1)

Combine like terms: 16 + 7 = 23
23 + -6y + 3y = 5(y + 1)

Combine like terms: -6y + 3y = -3y
23 + -3y = 5(y + 1)

Reorder the terms:
23 + -3y = 5(1 + y)
23 + -3y = (1 * 5 + y * 5)
23 + -3y = (5 + 5y)

Solving
23 + -3y = 5 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
23 + -3y + -5y = 5 + 5y + -5y

Combine like terms: -3y + -5y = -8y
23 + -8y = 5 + 5y + -5y

Combine like terms: 5y + -5y = 0
23 + -8y = 5 + 0
23 + -8y = 5

Add '-23' to each side of the equation.
23 + -23 + -8y = 5 + -23

Combine like terms: 23 + -23 = 0
0 + -8y = 5 + -23
-8y = 5 + -23

Combine like terms: 5 + -23 = -18
-8y = -18

Divide each side by '-8'.
y = 2.25

Simplifying
y = 2.25

See similar equations:

| x^5+9x=0 | | 0=-t^2+6t | | T^4-8T^3-T+8= | | Y=90x | | =5x+6x | | 3/4+1/4=3/4-1/4 | | y=(ln(8x+5))(x^4) | | a+4a+32=12 | | 3+-4d=13 | | -7(11z+5)=5(-15z-7)-2z | | 3x^2+5x=8x | | 16+8y=8(y+2) | | 12a+2=6-7a | | 4(-6j+16)=3(-8j+3) | | log(4)(5x-13)=2 | | 3x^2+22+7=0 | | 3-4x=2-3x | | -40x-45+63x+27=-x+3x+9 | | -20p+4=4(-5p+1) | | =4(2+4k)+(7k+1)8 | | =(ln(8*x+5))(x^4) | | D=(ln(8*x+5))(x^4) | | 6=-3t^2+36t | | -6(-10-15w)=5(18w+12) | | 2x^2+y^2+2xy-2x=-1 | | 3t^2-11t+6= | | 14v+7=-7(-2v-1) | | y=(ln(8*x+5))(x^4) | | =7(7+8k)+3(k+5) | | 17g+48=8(8g-11)-13g | | 3=(1/2)b+11 | | 2(-u-19)=-2+u |

Equations solver categories